Effects of atorvastatin added to inhaled corticosteroids on lung function and sputum cell counts in atopic asthma. Issue 12 (29th August 2008) - Hothersall, E J; Chaudhuri, R; McSharry, C; Donnelly, I; Lafferty, J; McMahon, A D; Weir, C J; Meiklejohn, J; Sattar, N; McInnes, I; Wood, S; Thomson, N C
Abstract : Background: Statins have anti-inflammatory properties that may be beneficial in the treatment of asthma. A study was undertaken to test the hypothesis that atorvastatin added to inhaled corticosteroids improves lung function and airway inflammation in atopic adults with asthma. Methods: 54 adults with atopic asthma were recruited to a double-blind randomised controlled crossover trial comparing the effect of oral atorvastatin 40 mg daily with that of a matched placebo on asthma control and airway inflammation. Each treatment was administered for 8 weeks separated by a 6-week washout period. The primary outcome was morning peak expiratory flow (PEF). Secondary outcomes included forced expiratory volume in 1 s, asthma control questionnaire score, airway hyper-responsiveness to methacholine, induced sputum cytology and inflammatory biomarkers. Results: At 8 weeks the change in mean morning PEF compared with baseline did not differ substantially between the atorvastatin and placebo treatment periods (mean difference −0.5 l/min, 95% CI −10.6 to 9.6, p = 0.921). Values for other clinical outcomes were similar between the atorvastatin and placebo treatment periods. The absolute sputum macrophage count was reduced after atorvastatin compared with placebo (mean difference −45.0×10 4 cells, 95% CI −80.1 to −9.7, p = 0.029), as was the sputum fluid leucotriene B4 (mean difference −88.1 pg/ml, 95% CI −156.4 to −19.9, p = 0.014). Conclusion: The addition of atorvastatin to inhaled corticosteroids results in no short-term improvement in asthma control but reduces sputum macrophage counts in mild to moderate atopic asthma. The change in sputum macrophage count suggests potential areas for investigation of statins in other chronic lung diseases.